Stock Price Reactions to The Wall Street Journal's Securities Recommendations - Liu, Pu; Smith, Stanley D.; Syed, Azmat A. (Journal of Financial and Quantitative Analysis, 1990)
Pu Liu, Stanley D. Smith, Azmat A. Syed, Stock Price Reactions to The Wall Street Journal's Securities Recommendations, The Journal of Financial and Quantitative Analysis, Vol. 25, No. 3 (Sep., 1990), pp. 399-410